RANCANG BANGUN SISTEM INFORMASI PENILAIAN HASIL BELAJAR SISWA BERBASIS WEB DI SDN PEKAYON JAYA VI BEKASI - Ayura Safa Chintami (2021)
SDN Pekayon Jaya VI Bekasi as one of the educational institutions, certainly has learning and teaching activities that is not able to be separated from the management of student learning outcomes. The institution manages 2013 curriculum-based assessments and implements them every six months. The unavailability of an effective system that accommodates the assessment process of student learning outcomes, which final result is the purpose's basis of this study. This research creates the information system's design for web-based learning outcomes of students at SDN Pekayon Jaya VI Bekasi. The programming language for this system uses the PHP language, database storage with MySQL, and the development of the system's design with the waterfall method. The stages of waterfall methods include analysis, design, programs, testing, and maintenance. The result of this study is the availability of an information system that can help the administration, homeroom teacher, and other teachers in carrying out their respective tasks related to the management of the student learning outcomes, as well as the availability of an information system to facilitate the student's guardian in viewing reports of the student's learning grades.